Osteoporotic distal femur fractures in the elderly: peculiarities and treatment strategies. - Canton, Gianluca; Giraldi, Gioia; Dussi, Micol; Ratti, Chiara; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2019)
Distal femur fractures account for 4-6% of osteoporosis related fractures of the femur in the elderly population. They represent a relevant cause of morbidity and mortality in the geriatric population with a reported 1-year mortality reaching 30%. Non-displaced fractures or even displaced fractures in patients with high operative risk can be treated conservatively. However, operative treatment is the most widely accepted management option for displaced fractures. The advantage resides in early mobilization and weight-bearing, reducing risks related with a prolonged immobilization when compared with conservative treatment. On the other hand, the intrinsic difficulty of fixing an osteoporotic bone is a major concern. The presence of osteosynthesis devices or prosthetic implants in the femur can make the surgical treatment more challenging, sometimes limiting therapeutic options. Aim of the present paper is to review the most recent literature about osteoporotic distal femur fractures in the elderly, including periprosthetic and other hardware related fractures, to highlight current evidence on management options and related results as a guide for the daily clinical practice.